Evaluation of Cardiorespiratory Function During Cardiopulmonary Exercise Testing in Untreated Hypertensive and Healthy Subjects - Zhang, Yahui; Jiang, Zhihao; Qi, Lin; Xu, Lisheng; Sun, Xingguo; Chu, Xinmei; Liu, Yanling; Zhang, Tianjing; Greenwald, Stephen E. (Frontiers in Physiology, 2018)
Objective: This study aimed to compare differences in cardiorespiratory function between untreated hypertensive subjects (UHS) and healthy subjects (HS) during cardiopulmonary exercise testing (CPET). Additionally, it also aimed to explore the potential mechanisms of different exercise responses in cardiorespiratory function before, during and after CPET. Methods: Thirty subjects (15 UHS and 15 HS) were enrolled. Photoplethysmography (PPG), respiratory signal and ECG were simultaneously collected while subjects were performing CPET. Fiducial points (a, b, c, d, e) were extracted from the second derivative of the PPG (SDPPG), and the ratios b/a, c/a, d/a, e/a and (b-c-d-e)/a (named Aging Index, AGI) were calculated as markers of systolic and diastolic function. Additionally, respiratory rate was calculated and analyzed. Results: Before CPET, there were no signi- ficant differences in b/a, d/a and AGI between two groups. However, after CPET, b/a (-0.9±0.19 vs.-1.06±0.19, p-value =0.03) and AGI (-0.49±0.75 vs. -1.15±0.59, p-value=0.011) of the UHS group were significantly higher than those of the HS. The d/a (-0.32±0.24 vs. -0.14±0.17, p- value=0.024) and c/a (-0.33±0.26 vs. -0.07±0.19, p-value=0.004) were significantly lower in UHS than those in HS. In contrast, before CPET, e/a (0.22±0.11 vs. 0.32±0.09, p-value=0.007) in UHS was significantly lower than that in HS, while after CPET there was no significant difference between the two groups in this variable. In addition, during CPET, AGI (p-value=0.003) and respiratory rate (p-value=0.000) in UHS were significantly higher in comparison with before CPET. Conclusions: Different exercise responses showed the differences of cardiorespiratory function between UHS and HS. These differences not only can highlight the CV risk of UHS, but also can predict the appearance of arterial stiffness in UHS. Additionally, during CPET, significant differences in AGI, autonomic nervous function and respiratory activity assessed by respiratory rate were found between the two groups in comparison with before CPET.